Identification of Key Genes Associated With the Process of Hepatitis B Inflammation and Cancer Transformation by Integrated Bioinformatics Analysis - Zhang, Jingyuan; Liu, Xinkui; Zhou, Wei; Lu, Shan; Wu, Chao; Wu, Zhishan; Liu, Runping; Li, Xiaojiaoyang; Wu, Jiarui; Liu, Yingying; Guo, Siyu; Jia, Shanshan; et al. (Frontiers in Genetics, 2021)
Background: Chronic infection of hepatitis B leads to potential carcinogenic microenvironment, increasing the risk of cancer. Therefore, there is an urgent need to identify new diagnostic and prognostic biomarkers. This study aims to identify potential key genes related to the pathogenesis and prognosis of hepatitis B-related progressive liver disease. Hepatocellular carcinoma(HCC) has become the main cause of cancer death worldwide. More than half of hepatocellular carcinoma developed from hepatitis B virus infection(HBV). The purpose of this study is to find the key genes in the transformation process of liver inflammation and cancer, and to inhibit the development of chronic inflammation and the transformation from disease to cancer. Methods: Through the integrated analysis of the gene expression profile data set and TCGA data, the differentially expressed genes of hepatitis B related progressive liver disease were screened. The key genes related to the pathogenesis and prognosis of hepatitis B-related progressive liver disease were determined by protein-protein interaction network and Cox proportional hazard model analysis.Two groups of GEO data (including normal/HBV and HBV/HBV-HCC) were selected for differential expression analysis. The differential expression genes of HBV-HCC in TCGA were verified to coincide with the above genes to obtain overlapping genes. Then, functional enrichment analysis, modular analysis and survival analysis were carried out on the key genes. Results: We identified five key genes (CDK1, MAD2L1, CCNA2, PTTG1, NEK2). These genes may be closely related to the pathogenesis of hepatitis B-related progressive liver disease. In addition, prognostic gene markers composed of PTTG1, MAD2L1, PCLAF, RRM2, TPX2, CDK1, NEK2, DEPDC1, and ZWINT were constructed, and they performed well in predicting overall survival.We identified nine central genes (CDK1, MAD2L1, CCNA2, PTTG1, NEK2) that may be closely related to the transformation of hepatitis b. The survival and prognosis gene markers composed of PTTG1, MAD2L1, RRM2, TPX2, CDK1, NEK2, DEPDC1 and ZWINT were constructed, which performed well in predicting the overall survival rate. Conclusion: The findings of this study have certain guiding significance for further research on the transformation of hepatitis B inflammatory cancer, inhibition of chronic inflammation and molecular targeted therapy of cancer.